Implementation Research Result About the Effect of Heavy Metal Cadmium on the Growth of Tiger Shrimp (Penaeus monodon) as Biology Learning Source For Environmental Pollution - Hidayah, Ma'rifatul; Riani, Etty; Khastini, Rida Oktorida; Sjaiffuddin, Sjaifuddin (Universitas Labuhanbatu, 2022)
Research results in the form of products and processes can be used as learning resources that can develop appropriate scientific abilities according to student needs. This study aims to analyze the results of research on the effect of heavy metal cadmium on the growth of tiger shrimp which is used as a source of learning biology. The research was conducted at the Department of Biology Education, FKIP Untirta and several state high schools in Banten Provice: SMAN 1 Anyer, SMAN 1 Cinangka, SMAN 4 Cilegon, and SMAN 5 Cilegon. The analysis process is carried out through stages: product identification and research processes, selection and modification of research results, as well as the application and development of research results as a source of biology learning contained in the Lesson Plan (RPP). The results of the study on the effect of heavy metal Cd on the growth of tiger prawns were in accordance with the sub-concept of environmental pollution contained in KD 3.11 and 4.11 in class X SMA. Environmental pollution that occurs can inhibit the growth of biota so that it can damage and disrupt the natural balance caused by contamination from heavy metal cadmium which is the subject of the learning process.